Tahap pengetahuan pelajar dalam industri sawit di Malaysia - Jusoh Mohd Abdullah, Che Omar Ahmad Raflis, Ahmad Azhar (Management Research Journal, 2017)
Tahap pengetahuan pelajar dalam industri sawit di Malaysia by Jusoh Mohd Abdullah, Che Omar Ahmad Raflis, Ahmad Azhar,